(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Recurrence of glomerulonephritis (GN) after kidney transplant (Tx) may be associated with allograft loss. This study aimed to evaluate the frequency and prognosis of de novo or recurrent post-Tx GN. Methods. We reviewed 1305 kidney Tx biopsy samples obtained between 2006 and 2020. The biopsy specimens were divided into post-Tx GN (recurrent or de novo) and control groups (i.e., no detectable GN in biopsy). Demographic and baseline characteristics of the patients and kidney survival rates were analyzed. Results. From 1305 kidney transplanted biopsies, 350 repeated biopsies for transplant rejection were excluded. Among 955 analyzed biopsies, (mean age: 40.4 ± 13.48 years, mean transplantation duration: 4.54 ± 3.98 years, 74.6% males), the frequency of GN was 10.78%. The most common recurrent post-Tx GN was IgA nephropathy (22.3%), followed by secondary focal segmental glomerulonephritis (FSGS, 19.4%), primary FSGS (19.4%), and membranous glomerulonephritis (17.5%). In the post-Tx GN group, the mean serum creatinine and proteinuria were 3.28 ± 1.97 mg/dL and 2730 ± 1244 mg/d at the biopsy time and 4.14 ± 1.86 mg/dL and 2020 ± 1048 mg/d, at the end of the study. There was a significant relationship between baseline serum creatinine and graft loss (P < .001). One-, five-, and ten-year graft survival rates were 97%, 81%, and 63% in the postTx GN, and 100%, 92%, and 59% in the control group. The median time to graft loss after biopsy, (graft survival after biopsy), was significantly lower in the post-Tx GN group (P < .000). The other accompanying factors had no significant impact on graft survival. Conclusion. The median time to graft loss after biopsy was significantly lower in post-Tx GN. Baseline serum creatinine had a significant association with graft loss. Optimal management of recurrent or de novo GN should be a main focus of post-transplant care. DOI: 10.52547/ijkd.7205